Financial Sanction, Exchange Rate Volatility and Macroeconomic Variables (Case of Iran) - Seyed Hossein Mirjalili; Mosayb Pahlavani; Samira Heydarian (Iranian Journal of Finance, 2025)
Financial sanctions have economic consequences for the oil-dependent economies. We examined the impact of financial sanctions on exchange rate fluctuations and macroeconomic variables in Iran. To this end, we employed a new Keynesian DSGE model. The results indicated that with the shock in foreign exchange, production (Y) and imports initially decreased. Oil production has shown a positive reaction initially and a negative reaction in the medium term, and after 7 periods, the effect of the shock has disappeared. The capital stock (K) also decreased initially, and in two periods, it reacted positively. In the tenth period, its effect disappeared, and in the long term, it became partially negative, and its effect disappeared. The inflation rate has decreased initially, and its effect disappeared over time. Consumption decreased, and after five cycles, the reaction became positive and then disappeared. The interest rate increased initially and then decreased, and in the 10th period, the shock effect disappeared. The exchange rate initially decreased and then increased after one period.
Keywords: 330; Financial Sanction; Exchange Rate; Oil Revenue; Volatility; Macroeconomic Variables